Predictors of Mental Health Symptoms, Automatic Thoughts, and Self-Esteem Among University Students. Issue 4 (August 2017) - Hiçdurmaz, Duygu; İnci, Figen; Karahan, Sevilay
University youth is a risk group regarding mental health, and many mental health problems are frequent in this group. Sociodemographic factors such as level of income and familial factors such as relationship with father are reported to be associated with mental health symptoms, automatic thoughts, and self-esteem. Also, there are interrelations between mental health problems, automatic thoughts, and self-esteem. The extent of predictive effect of each of these variables on automatic thoughts, self-esteem, and mental health symptoms is not known. We aimed to determine the predictive factors of mental health symptoms, automatic thoughts, and self-esteem in university students. Participants were 530 students enrolled at a university in Turkey, during 2014–2015 academic year. Data were collected using the student information form, the Brief Symptom Inventory, the Automatic Thoughts Questionnaire, and the Rosenberg Self-Esteem Scale. Mental health symptoms, self-esteem, perception of the relationship with the father, and level of income as a student significantly predicted automatic thoughts. Automatic thoughts, mental health symptoms, participation in family decisions, and age had significant predictive effects on self-esteem. Finally, automatic thoughts, self-esteem, age, and perception of the relationship with the father had significant predictive effects on mental health symptoms. The predictive factors revealed in our study provide important information to practitioners and researchers by showing the elements that need to be screened for mental health of university students and issues that need to be included in counseling activities.